(untitled) (Journal of actual problems of jurisprudence, 2018)
In the 20th century, the rapid development of medicine, including reproductive medicine, began in the developed countries. It did not bypass the CIS countries. The article is devoted to the issues of surrogate motherhood in the context of the new criminal legislation of the Republic of Kazakhstan. Surrogate motherhood generally describes all cases when conception, bearing and birth of a child are carried out by a woman with the aim to passhim/her to other people for adoption. A surrogate mother is a woman who carries a child for a sterile couple before a child is born, in the absence of a genetic link with this child. Recently the institution of surrogate motherhood is the most intensively and comprehensively discussed problem of morality and law. Criminal Code of the CIS countries contain elementsrelated to surrogate motherhood, which our Criminal Code lacks. Protection of reproductive health should be implemented by all means, including criminal law. The introduction of similar norms in our Criminal Code of the Republic of Kazakhstan should help prevent the medical violations. At the same time, the solution of most of the problematic issues discussed above is the Code of the Republic of Kazakhstan «About Health Care and the Health System», which also needs further modernization. Кey words: surrogate maternity, criminal law, reproductive health, reproductive rights of women and men.